PTERYGIUM-a case report - Cheleva, Vesna; Ivanovska M.; Antova M; Dzajkovska E (My University, 2006)
A sporadic case of bilateral nasal and temporal pterygium on both eyes is present in this abstract. After four operations on all pterigia with limbal conjunctival autotransplantation from superior and inferior part of the bulbar conjunctiva there was no recurrence of the pterygium. The postoperative vision was improved. Pathohistological investigation of the pterygium samples confirmed the diagnosis.
Keywords: pterygium; limbal conjunctival auto transplantation; histopathology of pterygium